Iron dextran and iron dextran-gentamycin combined, compared as methods of preventing iron-deficiency anemia in neonatal pigs - Schoneweis, D.A.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Giving an iron iron dextran-gentamycin combination to young pigs had no advantages over giving them iron dextran alone, as measured by hemoglobin levels, packed cell volumes, or weight (when 28 days old).
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Iron dextran; Iron dextran-gentamycin; Iron-deficiency anemia; Neonatal pigs